ANALISIS KEAMANAN STRUKTUR BENDUNGAN DAN UNDERGROUND POWER HOUSE PLTA CIRATA JAWA BARAT - Indah Handayasari; Irma Sepriyanna; Nanda Yogi Setiyanto (FORUM MEKANIKA, 2017)
PT PJB BPWC as the manager of important buildings in the Cirata hydro power plant such as dams, dam control centers, spillway buildings, power houses, hillbones and others, in its operation requires monitoring to know the changes and behavior of the monitored buildings. Monitoring is done by observing certain locations regularly and continuously through the aid of tools / instruments or visually. PLTA Cirata installed about 20 types of instrumentation in the dam and underground power house which is used to monitor the security level of Cirata hydropower building structure. Monitoring and maintenance activities are intended to identify early symptoms of movement and changes that could endanger dam structures, other major structures, as well as to things that could threaten the safety of the human psyche so that preventive action can be taken to avoid further damage or loss big. Based on the fifth measurement of seepage instrumentation, inclinometer, piezometer, jointmeter, and crackmeter showed results that are in the range of values below the design boundary so it can be concluded that the safety conditions of the dam structure and underground power house PLTA Cirata are still safe.